2017
DOI: 10.1186/s12904-017-0238-4
|View full text |Cite
|
Sign up to set email alerts
|

Self-management support and eHealth for patients and informal caregivers confronted with advanced cancer: an online focus group study among nurses

Abstract: BackgroundSelf-management by patients and informal caregivers confronted with advanced cancer is not self-evident. Therefore they might need self-management support from nurses. This article reports on nurses’ perspectives on self-management support for people confronted with advanced cancer, and nurses’ experiences with eHealth in this context.MethodsSix online focus groups were organized, with a total of 45 Dutch nurses with different educational levels and working in different care settings. Nurses were ask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
14

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 35 publications
0
42
0
14
Order By: Relevance
“…Using the 5A model turned out to be difficult as it was new to the nurses. Previous studies’ results were comparable, as the last 2 A’s ( assist and arrange ) seem to be delivered least often by nurses [19,29,30]. However, those components are most important for producing meaningful and lasting behavioral changes [19].…”
Section: Discussionmentioning
confidence: 80%
“…Using the 5A model turned out to be difficult as it was new to the nurses. Previous studies’ results were comparable, as the last 2 A’s ( assist and arrange ) seem to be delivered least often by nurses [19,29,30]. However, those components are most important for producing meaningful and lasting behavioral changes [19].…”
Section: Discussionmentioning
confidence: 80%
“…Another barrier to adopt Oncokompas relates to the concept of self-management: some hospitals questioned whether access to an online self-management tool should be provided through a hospital or directly to patients themselves. More research is needed on the organization of self-management (support) in cancer care [27], but a key aspect in providing this support is cooperation between health services [28]. Also, in a previous qualitative study exploring HCP’s perspective regarding Oncokompas implementation, we found that all participants indicated that when Oncokompas was to be implemented in daily clinical practice, it should be offered to survivors through a clinical procedure in a care pathway [11].…”
Section: Discussionmentioning
confidence: 99%
“…The 5 A's framework has become a universal approach to encouraging behavioral change, including in smoking, nutrition, alcohol, and physical activity 13 . Figure 1 shows the five steps of the 5 A's model 22 : 1) Assess the subject's beliefs, behavior, and knowledge; 2) Advise the subject by providing specific information about health risks and the benefits of change; 3) Agree to collaboratively set goals based on the subject's interest and confidence in their ability to change their behavior; 4) Assist in identifying personal barriers, strategies, problem-solving techniques, and social/environmental support; 5) Arrange a plan for follow-up, such as visits, phone calls, and mailed reminders.…”
Section: Methodsmentioning
confidence: 99%